Comparison of intra- and interspecies nuclear transfer techniques in the production of cloned caprine embryos - Abdullah, Ramli; Kwong, P.J.; Khadijah, W.E.W. (2011)
Among the ARTs that are applied in goat farming industry, reproductive cloning technology in production of cloned goat embryos are foreseen to facilitate the effort of mass goat production in just a short time frame. There are two possible approaches that can be applied to produce cloned embryos, namely intraspecies SCNT (intraSCNT) and interspecies SCNT (interSCNT). The application of interSCNT is known to play vital role in species preservation, livestock propagation and therapeutic cloning. In fact, the application of interSCNT approach to produce cloned caprine embryos has not been reported at present. The prospect of this application can be seen to overcome the relative difficulty of obtaining caprine oocytes to be used as recipient cytoplasm in the cloning protocol. Several studies have shown that ooplasm of bovine can support early development of embryos produced by nuclear transfer using somatic cell nuclei derived from different mammalian species such as sheep, pigs and rats. Therefore, this present study was conducted with the aim to produce cloned caprine embryos using intraSCNT versus interSCNT technique. As a control to this experiment, bovine intraSCNT was conducted. The source of bovine and caprine oocytes was obtained from the abattoir-derived ovaries and also via laparoscopy ovum pick-up (LOPU) technique on superovulated does. The collected oocytes were subsequently cultured in in vitro maturation medium for 18-22 h. The matured oocytes were then subjected to enucleation process. The enucleated oocytes were then injected with either a male ear fibroblast cell from caprine or bovine. The couplets were electrofused and chemically activated before in vitro cultured. The results for fusion rate of caprine interSCNT (64.2%) was significantly lower compared to the caprine intraSCNT (81.9%). The reconstructed caprine oocytes derived from interSCNT approach seemed to have the developmental efficiency that is comparable to the intraSCNT approach as the cleavage rate of both caprine intra(48.9%) and interSCNT (51.3%) embryos did not differ significantly. The in vitro development of caprine interSCNT could not go beyond morula stage. Therefore the comparison of the in vitro developmental rate of cloned bovine and caprine embryos using the intra- and interSCNT approach was made up to morula stage. The percentage of cloned caprine embryos developed to morula using intra- (20.6%) and interSCNT (6.9%) approach did not differ significantly. However, the percentage of cloned bovine morula derived from intraSCNT approach (46.1%) was significantly higher. Generally, caprine embryos are known to have a lower in vitro developmental potential towards the late perimplantation stage. Even the reports of success in producing cloned kids involved the transfer of embryos at early cloned embryos stages from 2 to 8 cell stages. In the nutshell, cloned caprine embryos can be produced via both intraSCNT and interSCNT approach. The efficacy of interSCNT approach is comparable to the intraSCNT approach in an effort to produce early preimplantation stages of cloned caprine embryos. (C) 2011 Elsevier B.V. All rights reserved.